ALTERNATIF UPAYA PENCEGAHAN KEJAHATAN MAFIA TANAH DALAM PERSPEKTIF HUKUM ADMINISTRASI PERTANAHAN - Vani Wirawan (Legal Standing : Jurnal Ilmu Hukum, 2023)
The existence of the land mafia has resulted in delays in the development of investment and economic growth because the crimes committed cover various land cases, so it is necessary to start prevention in the area of land administration. This study aims to develop efforts to prevent land mafia in the area of land administration. This research is descriptive analytical with a socio-legal approach. The results of this study obtained alternative efforts to prevent the land mafia, namely the idea of changing land registration from a negative publication system to a positive publication system. However, if the publication system is positive that there is an error in the registration procedure, resulting in losses for parties who may be more entitled, the state guarantees a compensation fund in the form of payment of compensation to the claimant whose rights are proven correct with the concepts of indefeasible and indemnity.